(untitled) (Journal of Informatics and Mathematical Sciences, 2020)
In this paper, we introduce and study a new subclass of meromorphic univalent functions defined by Bessel function. We obtain coefficient inequalities, extreme points, radius of starlikeness and convexity. Finally, we obtain partial sums and neighborhood properties for the class \(σ _p ^* ( η, k, λ, υ)\).